Challenges Resulting from Healthcare induced Demand: a qualitative study - Mahmoud Keyvanara (مدیریت اطلاعات سلامت, 2013)
Introduction: Induced demand is one of the challenges of health care systems in different countries. It increases health care costs and also increases catastrophic cost index. This article seeks to examine the challenges of induced demand with the use of expert’s experiences of Isfahan University of Medical Sciences.